The indigenous people of the Caribbean - Wilson, Samuel M. (Ripley P. Bullen series., 1997)
"This volume brings together nineteen Caribbean specialists to produce the first general introduction to the indigenous peoples of that region. Writing for both general and academic audiences, contributors provide an authoritative, up-to-date picture of these fascinating peoples - their social organization, religion, language, lifeways, and contribution to the culture of their modern descendants - in what is ultimately a comprehensive reader on Caribbean archaeology, ethnohistory, and ethnology."--Jacket.